Global Communication as Herald of Global Citizenship - Ugondo, Peter Iorper; Gana, Stephen Victor; Inobemhe, Kelvin (PT. Riset Press International, 2025)
In an era characterised by unprecedented interconnectedness and rapid technological advancements, global communication emerges as a pivotal force shaping contemporary notions of citizenship. The transformative role of global communication in heralding a new era of citizenship, one that transcends traditional boundaries and fosters inclusive engagement on a global scale is the focus of this study. The study is anchored on an interdisciplinary theoretical framework such as the network society theory, theory of global citizenship, and the agenda-setting media theory. The study is based on a survey-based approach and relied on questionnaire as instrument of data collection. Findings showed that there is relationship between global communication and global citizenship. However, the study also showed that factors that influence individuals' perception of identity are in the form of diverse cultures, globalisation and international trade (economic factors), social interactions, media representations, and political events as well as social issues. Furthermore, the study revealed that social media and related technology have promoted global awareness and citizen engagement. Researchers concluded that global communication serves as a herald of citizenship by facilitating cross-cultural dialogue, empowering civic engagement, and fostering a sense of global belonging. Embracing the transformative potential of global communication offers new opportunities for building a more inclusive, empathetic, and socially responsible form of citizenship in the 21st century. It was recommended, among others, that government and other stakeholders must promote digital inclusion through digital literacy programmes across underserved communities.